Alterations in RDINK4/ARF‐mediated en bloc regulation of the INK4‐ARF locus in human squamous cell carcinoma of the head and neck. Issue 7 (2nd December 2013) - Poi, Ming J.; Knobloch, Thomas J.; Sears, Marta T.; Warner, Blake M.; Uhrig, Lana K.; Weghorst, Christopher M.; Li, Junan
<x xml:space="preserve">Abstract</x> The presence of RDINK4/ARF (RD) enhancer in the INK4‐ARF locus provides a novel mechanism to simultaneously increase the transcription of p15INK4b (p15), p14ARF (p14), and p16INK4a (p16). While such upregulation can be repressed through interactions between RD and oncoproteins CDC6 and BMI1, little is known about the involvement of RD in cancer. In this study we investigated RD deletions in 30 squamous cell carcinoma of the head and neck (SCCHN) and the patient‐matched High At‐Risk Mucosa specimens (HARM, "phenotypically normal" tissues neighboring SCCHN foci but beyond the surgical resection margin). RD was deleted (homozygously/heterozygously) in SCCHN and HARM at the incidence of 36.7% (11/30) and 13.3% (4/30), respectively. In comparison, no RD deletion was detected in 26 oral buccal brush biopsy specimens from healthy donors. Both p16 and p14 were lowly expressed in SCCHN and HARM, and their mRNA expression levels were positively associated with each other (P < 0.01). Moreover, BMI1 was highly expressed in both SCCHN and HARM, and BMI1 overexpression was associated with p16 downregulation in SCCHN (P < 0.05). These results indicate that RD deletion and BMI1 overexpression frequently occur in the early stage of oral carcinogenesis and BMI1 overexpression may downregulate the transcription of p16 and p14 through interfering with RD. © 2013 Wiley Periodicals, Inc.